Cobalt bullets for beef cattle - Richardson, D.; Smith, E.F.; Brethour, J.R.; Koch, B.A.; Tsien, W.S.; Carmack, B.D.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Cobalt is a trace mineral element which is essential to the health and well-being of animals. If it is deficient in the ration, it should be supplied. A cobalt bullet, which is placed in the rumen, was developed in Australia for sheep and cattle on cobalt-deficient pastures or rations. These cobalt bullets were found to be effective in preventing cobalt deficiency. Cobalt bullets are now available in this country. The bullet is composed of 90% cobalt oxide and 10% binding agent. The weight is 20 grams for cattle and 5 grams for sheep. The bullet is placed in the rumen with a balling gun. Since it is heavy, it remains in the rumen and allows cobalt to become available to the animal. Bullets were recovered at slaughter in some of these tests after over 300 days.
Keywords: Beef; Cobalt bullets; Rumen; Deficiency